A thermo-activated wall for load reduction and supplementary cooling with free to low-cost thermal water. (15th March 2016) - Yu, Yuebin; Niu, Fuxin; Guo, Heinz-Axel; Woradechjumroen, Denchai
Abstract: A building envelope serves as a thermal barrier and plays an important role in determining the amount of energy used to achieve a comfortable indoor environment. Conventionally, it is constructed and treated as a passive component in a building thermal energy system. In this article, a novel, mini-tube capillary-network embedded and thermal-water activated building envelope is proposed to turn the passive component into active, therefore broaden the direct utilization of low-grade thermal energy in buildings. With this proposed approach, low-grade thermal water at a medium temperature close to the ambient environment can be potentially utilized to either counterbalance the thermal load or indirectly heat and cool the space. With the revealing of the idea, effects of water temperature and flow rate on the envelope's thermal performance are investigated using a transient model. The results indicate that the thermo-activated wall can be effective in stabilizing the internal surface temperature, offsetting the heat gain, and supplying cooling energy to the space in summer. Utilization of the innovation should take the cost of total energy, energy benefit and efficiency into consideration. This article illustrates how low-grade energy can be actively used as a means for achieving net-zero energy buildings. Highlights: We propose an innovative building envelope system for low-grade energy use. The building envelope can be easily thermo-activated with low-cost thermal water. The transient simulation model is developed to study the dynamics and performance. The system is effective in reducing thermal load and suppling energy at low-cost.